VqBGH40a isolated from Chinese wild Vitis quinquangularis degrades trans-piceid and enhances trans-resveratrol - Yan, Chaohui (Plant science : an international journal of experimental plant biology, 2021)
Copyright © 2021 Elsevier B.V. All rights reserved.